Evaluation of Building Displacement Induced By EPB Tunneling Through GPS-GNSS Monitoring System and Back Analysis Technique (Tabriz Subway Twin Tunnels) - Seyed Morteza Davarpanah; Mostafa Sharifzadeh; Javad Sattarvand; Samad Narimani (Civil Engineering Journal, 2016)
One of the main aspects of tunneling in urban areas is controlling the amount of settlement that might cause some damage to the structures and infrastructures. In this paper, the novel displacement monitoring system called Global Positioning System - Global Navigation Satellite System (GPS-GNSS) has been applied to monitor the building displacement .One of the most important features of this approach is that this system provides three dimensional displacement behavior of the building. Besides, in order to fulfill the purpose of accuracy, the amount of settlement induced by Earth Pressure Balance (EPB) tunneling was calculated by numerical, empirical and analytical methods. In order to achieve this purpose, the back analysis technique was considered. The order in which the geotechnical parameters are optimized depends on the amount of sensitivity function. That is, the parameter of high sensitivity function is optimized first. According to the calculations, the sensitivity analysis results show that the maximum amount of sensitivity function with the volume loss of more than 1% in respect to the internal friction angle is about 0.5, which is greater than other geotechnical properties. According to the results of back analysis technique, the optimized geotechnical properties were elastic modulus (), internal friction angle () and cohesion () found on the volume loss of 1.5% with less than 0.02% error. The maximum settlement of the building at the studied area, explored by the optimized numerical method, is about 4 mm, which is in the range of monitored data (3mm-13mm) obtained through GPS-GNSS procedure.